PENGARUH KOMPETENSI, MOTIVASI KERJA DAN DISIPLIN KERJA TERHADAP KINERJA GURU (Studi Kasus Di Smk Karya Fajar Kecamatan Petir Kabupaten Serang Provinsi Banten) - Jamaludin, J; Pawirosumarto, Suharno (SWOT : Jurnal Ilmiah Ilmu Manajemen, 2019)
This research was aimed to know the influences of competence, work motivation and Work Discipline towards teacher’s Performance at Vocational High school Karya Fajar, Petir district, Serang Regency, Banten Province. The type of this research was quantitative research using survey approach. The research population  of all teachers at Vocational High school Karya Fajar with amount 30 persons. Sampling technique used in this research was technique Non Probability sampling with saturation sampling where all populations to be sample. The data analysis used multiple linear regression analysis (t-test and F-test) with SPSS program 22 version. The results showed competence has positive and significant effect to teacher’s performance. Work Motivation has positive and significant effect to teacher’s performance. Work discipline has positive and significant effect to teacher performance. The competence, work motivation and work discipline simultaneously (simultaneous) positive and significant effect on teacher’s performance. Based on the results of study were advised: teachers have to master professional competence well. School should be able to create safe feeling towards teacher. Teachers should have a goal and competence to be achieved in learning